Peranan Manajemen Sarana Dan Prasarana Dalam Meningkatkan Mutu Pembelajaran Di MTS. Madang Suku 1 - Wewen Andrianto; Ayu Lestari (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang OKU Timur Sumatera Selatan, 2023)
This study aims to determine the role of facilities and infrastructure management in improving the quality of learning in MTs. Madang Tribe 1. The method used in this study is a qualitative research method, namely a descriptive approach, in the form of data in the form of subject information, descriptions of words or sentences. Then in the data collection technique the authors carried out three data collection techniques namely observation, interviews, and documentation. Then the data that has been obtained from the three techniques are analyzed using data analysis, namely through the process of data classification, data categorization, drawing conclusions, and verification. The results of the research based on data from observations, interviews, and documentation show that the facilities and infrastructure management activities in MTs. Madang Suku 1 is carried out through 4 stages, namely: planning, procurement, maintenance and removal of facilities and infrastructure. Management planning for facilities and infrastructure in improving the quality of learning in MTs. Jaya Bakti is carried out with deliberations (meetings). Procurement of facilities and infrastructure in improving the quality of learning at MTs Jaya Bakti is carried out by the teacher first proposing what facilities and infrastructure are needed to WKM facilities and infrastructure, then WKM submits them to the school principal. Maintenance (care) is carried out by the entire madrasah community. Elimination of existing facilities and infrastructure at MTs. Jaya Bakti what to do if the sarpras can no longer be used and is badly damaged. The quality of learning in MTs. Madang Tribe 1 has more influence on teachers, students, and facilities and infrastructure. In implementing the management of educational facilities and infrastructure in improving the quality of learning in MTs. Madang Tribe 1 dominates the inhibiting factors.